The Role of Language in Character Formation Thorugh The Perspective of The Qur’an - Maulidah Rizkiyah; Siti Nurjannah; Sumedi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to elaborate the role of language in character formation through the perspective of the Qur'an. Human life cannot be separated from language because all human activities allow the use of language. This research uses the literature review method to obtain the data. The result of this study is that language functions as a tool of social control that shapes character influencing people's attitudes and behavior. Use of language that 2 Good and right can prevent conflict and strengthen relationships between individuals. Religious teachings such as the Quran emphasize the importance of speaking well and politely, which is part of character building. Good mastery of Indonesian also plays a role in the development of intelligence and personality. Language learning which includes listening, reading, speaking, and writing helps instill character values such as honesty, responsibility, and courtesy. Environmental, emotional, and social factors influence the use of coarse language, so it is important to teach verbal control early. Thus, language is not only a means of communication but also a reflection of one's morals and character.